Persamaan Nilai Korelasi Indeks Plastisitas (PI) Tanah Dengan California Bearing Ratio (CBR) Tanah Lempung Palangka Raya - Noviyanthy Handayani; Norseta Ajie Saputra (Media Ilmiah Teknik Sipil, 2019)
During this time to get the value of California Bearing Ratio (CBR) planners will conduct field tests and/or laboratory tests. This takes time and is relatively large. For this reason, it is needed a practical matter or formulation about the relationship between soil parameters so that planners do not need to test the overall soil parameters. This study aims to obtain a graph or correlation of the Plasticity Index (PI) with California Bearing Ratio (CBR) for clay soils in the Palangka Raya region. Clay soil samples were taken at 3 (three) locations in the City of Palangka Raya. Based on the results of tests on several samples obtained the largest CBR value in soil samples from Tangkiling village which reached a value of 6.56%. While the lowest CBR value obtained from the village of Kereng Bengkirai is 3.14%. For the PI value, the biggest value obtained in Bukit Rawi village is the largest, namely 20.54% and the smallest PI value obtained in Tangkiling village is 9.01%. In general, it can be concluded that the CBR value of clay is inversely proportional to the value of PI. Wherein it is known that the greater the CBR value, the smaller the PI value and vice versa. The overall correlation results of the PI value (plasticity index) to the CBR (California Bearing Ratio) obtain the correlation results using the linear graph CBR = -0.28383 PI + 8,9843. While the correlation value based on analytical calculations obtained CBR = -0,3006X + 9,0190. This test shows that the correlation value has a very high relationship when viewed from the benchmark correlation results (R = 0.80-1.00). The results of the correlation value using linear regression graphs worth R = 0.8489 and using analytical correlation methods worth R = 0.9283. So the final result of this study is to look for a relationship between PI values ​​and CBR values. Then for the value of R is taken the smallest value that is R = 0.8489.